Behroonguda: a race success story in joint forest management - D'Silva, Emmanuel; Nagnath, B. (2002)
Behroonguda is one of 77,000 hamlets and villages in Andhra Pradesh. The 97 families who belong to the Gond and Naikpod tribes formed themselves into a forest protection group in 1990, but the state government officially recognised their efforts in 1993. In 1998, five years after the recognition of the committee - referred to as Vana Samarakshana Samithi, or VSS - Behroonguda residents began to derive usufruct benefits from the forest. The case study documents the efforts of the villagers, the cots they have borne and the benefits they have derived from protecting 500 hectares of degraded forest allotted to them as part of the joint forest management (JFM) in Andhra Pradesh. The VSS is widely regarded as being successful. The paper analyses the reasons for the success of JFM and compares the experience of Behroonguda with other similar experiments in other countries to draw important lessons. The paper strikes one discordant note: The people of Behroonguda have not been clearly told when the forest department's financial and technical support would end. For JFM to be sustainable, it is important that forest staff be redeployed to other needy communities and the financial support to silvicultural and other conservation activities be discontinued. Only then will the Behroonguda experiment be deemed fully successful and sustainable. - Reproduced.
Keywords: Forest management